2005
DOI: 10.1007/s10488-005-3265-z
|View full text |Cite
|
Sign up to set email alerts
|

Best practices for assessing competence and performance of the behavioral Health workforce

Abstract: The need for mechanisms to assess the competence and performance of the behavioral health workforce has received increasing attention. This article reviews strategies used in general medicine and other disciplines for assessing trainees and practitioners. The possibilities and limitations of various approaches are reviewed, and the implications for behavioral health are addressed. A conceptual model of competence is presented, and practical applications of this model are reviewed. Finally, guidelines are propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 38 publications
0
39
0
2
Order By: Relevance
“…14,15 Furthermore, academics confirmed that the blueprint helps in ensuring that analysis, evaluation, and synthesis skills are covered. 2,9,16 Academics reported that test blueprint served as a map to establish the total weightage for each content domain and proportion of test items assigned for each sub-category of a test according to modified Bloom's taxonomy. 7,17,18 Academics are in agreement that efforts put in having good blueprint improves test content validity which improves score interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…14,15 Furthermore, academics confirmed that the blueprint helps in ensuring that analysis, evaluation, and synthesis skills are covered. 2,9,16 Academics reported that test blueprint served as a map to establish the total weightage for each content domain and proportion of test items assigned for each sub-category of a test according to modified Bloom's taxonomy. 7,17,18 Academics are in agreement that efforts put in having good blueprint improves test content validity which improves score interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…20 MCQs exams that satisfy the difficulty and discrimination indices are considered as well-structured and can reliably be administered on large scale to students as well as health care providers. 1,2,21,22 There is consensus among academics that the level of difficulty should be considered when designing the blueprint since the objectives needed from courses taught at early years of study emphasizes on knowledge acquisition while the objectives at the end of the program emphasizes on critical thinking skills. 12,13,23,24 Therefore, the MCQs exam should have a higher percentage of questions in the analysisevaluation and evaluation-synthesis spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The standardized written MCQs exams are considered as the gold standard to assess the knowledge acquisition. [1][2][3][4][5] The licensure or certifying boards, in every particular field speciality, are responsible for developing and administering the MCQs exams. The MCQs exams could be administered on paper or delivered on a computer.…”
Section: Introductionmentioning
confidence: 99%